Epigenetic landscape of the TERT promoter: a potential biomarker for high risk AML/MDS. (19th July 2016) - Zhao, Xin; Tian, Xin; Kajigaya, Sachiko; Cantilena, Caroline R.; Strickland, Stephen; Savani, Bipin N.; Mohan, Sanjay; Feng, Xingmin; Keyvanfar, Keyvan; Dunavin, Neil; Townsley, Danielle M.; Dumitriu, Bogdan; et al.
Summary: Although recent observations implicate the importance of telomerase activity in acute myeloid leukaemia (AML), the roles of epigenetic regulations of the TERT gene in leukaemogenesis, drug resistance and clinical prognosis in AML are not fully understood. We developed a quantitative pyrosequencing‐based methylation assay covering the TERT proximal promoter and a partial exon 1 ( TERT pro/Ex1) region and tested both cell lines and primary leukaemia cells derived from AML and AML with preceding myelodysplastic syndrome (AML/MDS) patients ( n = 43). Prognostic impact of methylation status of the upstream TERT promoter region was assessed by the Kaplan–Meier method. The activity of the telomerase inhibitor, imetelstat, was measured using leukaemia cell lines. The TERT pro/Ex1 region was highly methylated in all cell lines and primary leukaemia cells showed diverse methylation profiles. Most cases showed hypermethylated regions at the upstream TERT pro/Ex1 region, which were associated with inferior patient survival. TERT pro/Ex1 methylation status was correlated with the cytotoxicity to imetelstat and its combination with hypomethylating agent enhanced the cytotoxicity of imetelstat. AML cell lines and primary blasts harbour distinct TERT pro/Ex1 methylation profiles that could serve as a prognostic biomarker of AML. However, validation in a large cohort of patients is necessary to confirm our findings.